2006
DOI: 10.1044/cicsd_33_f_138
|View full text |Cite
|
Sign up to set email alerts
|

Computer Use in the Management of Aphasia: A Survey of Practice Patterns and Opinions

Abstract: Computers are involved in many facets of daily life, and studies have shown computers to be effective tools in aphasia rehabilitation. However, the degree to which speech-language pathologists (SLPs) use computers in aphasia management is unclear. This study surveyed SLPs to determine patterns and frequency of computer use associated with aphasia rehabilitation. The survey was distributed to SLPs in health care settings through e-mail and traditional mail. Surveys were analyzed for frequency and patterns of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…One of the main barriers to rehabilitation through technology for individuals with aphasia is a lack of accessible training and support for both people with aphasia (Finch & Hill, 2014;McCall, 2012;Parr, 2007) and SLT clinicians (Davis & Copeland, 2006). Individuals with aphasia often face significant barriers to computer training due, for example, to impaired comprehension of spoken/written verbal commands, difficulty asking questions, and writing deficits (Lazar & Antoniello, 2008;Elman, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the main barriers to rehabilitation through technology for individuals with aphasia is a lack of accessible training and support for both people with aphasia (Finch & Hill, 2014;McCall, 2012;Parr, 2007) and SLT clinicians (Davis & Copeland, 2006). Individuals with aphasia often face significant barriers to computer training due, for example, to impaired comprehension of spoken/written verbal commands, difficulty asking questions, and writing deficits (Lazar & Antoniello, 2008;Elman, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…However, basic computer skills are an essential precursor to accessing potentially intensive, effective therapy, therefore any ICT illiteracy of this client group and requirements for follow-up support must be targeted if they are to be able to access such rehabilitation. The clinician must therefore consider expanding the range of technology uses in aphasia rehabilitation to span the disorder-orientated, functional treatment and social participation aspects of care (van de Sandt-Koenderman, 2011), although it is acknowledged that clinicians may themselves need training and support in their use of technology in aphasia rehabilitation (Davis & Copeland, 2006). This research developed a bespoke computer course that aimed to narrow the 'digital divide'…”
Section: Discussionmentioning
confidence: 99%
“…However, with the increasing permeation of technology into aspects of daily life (including work, shopping, finance and social contact), computers are also becoming increasingly encountered in the clinical setting, including during aphasia rehabilitation. In the United States, Davis and Copeland (2006) found that 51.4% of SLPs surveyed reported using computers in aphasia rehabilitation. This recent, rapid development and uptake of technology in aphasia rehabilitation is also reflected in the wide variety of therapy apps and software, and in the dedication of special issues of professional journals to the area (e.g., Kurland, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the administrative advantages (Davis & Copeland, 2006), the potential benefits of computers (and other electronic devices) in aphasia rehabilitation include the ability to: (1) increase therapy intensity (Finch, Clark, & Hill, 2013; Palmer, Enderby, & Paterson, 2013; Wade, Mortley, & Enderby, 2003); (2) maximise the number of items and tasks (Adrian, Gonzales, & Buiza, 2003; Adrian, Gonzalez, Buiza, & Sage, 2011; Wade et al, 2003); (3) extend the duration of rehabilitation (Fink, Brecher, Sobel, & Schwartz, 2005); and (4) enable rural and remote patients to receive a speech pathology service without a clinician being physically present. This latter point is particularly pertinent for countries such as Australia, which are vast in size with a large rural population.…”
Section: Introductionmentioning
confidence: 99%
“…In a survey of US speech-language pathologists (SLPs), Davis and Copeland (2006) found that more than 50% of respondents used computers in aphasia treatment, including treating reading, writing and word-finding difficulties. Assessing aphasia using computers is less common, though with increasing pressures on SLP services in terms of both staff numbers and staff time, computer-delivered assessment may have great potential to relieve some of those pressures and bring both financial and administrative advantages.…”
Section: Introductionmentioning
confidence: 99%